Comparison of second-line on-site computed quantitative flow ratio from coronary computed tomography angiography to PET perfusion imaging for detecting obstructive coronary artery disease. (3rd October 2022) - Dahl, J; Ramussen, L D; Ding, D; Westra, J; Wijns, W; Tu, S; Christiansen, E; Eftekhari, A; Gormsen, L C; Ejlersen, J A; Winther, S; Bottcher, M
Abstract: Introduction: In patients with suspected obstructive coronary artery disease (CAD) on coronary computed tomography (CTA), guidelines endorse second-line selective testing for hemodynamic evaluation of suspected CAD. A variety of non-invasive modalities are available, and myocardial perfusion imaging with Rubidium-82 positron emission tomography (PET) is an established method with high diagnostic performance. Recently, an on-site method estimating computed tomography-derived quantitative flow ratio (CT-QFR) showed promising results for discriminating obstructive CAD. However, no study has compared the diagnostic performances of PET and CT-QFR. Purpose: To assess a possible non-inferiority of CT-QFR compared to PET in patients with suspected obstructive CAD at CTA using invasive coronary angiography (ICA) with fractional flow reserve (FFR) as reference. Methods: Patients (n=1732, 57% males, age 59±9.5) referred on a clinical indication with symptoms suggestive of obstructive CAD underwent routine CTA. Patients with ≥50% diameter stenosis (DS) on CTA were referred for PET and subsequent ICA with FFR. CT-QFR was analyzed post-hoc blinded to PET and ICA results. Abnormal CT-QFR was defined as CT-QFR ≤0.80 in any vessel with a diameter ≥1.5mm. An independent core-lab evaluated PET scans as abnormal/normal with optional analyst-dependent application of pre-specified criteria; summed stress score of ≥4 in ≥2 contiguous segments, vessel-specific myocardial blood flow (MBF) <2.00 ml/g/min, global myocardial blood flow reserve ≤1.8, and/or transient ischemic dilatation ratio >1.13. Obstructive CAD was defined as ICA with FFR ≤0.80 or high-grade stenosis (≥90% DS). Results: In total, 445/1732 patients (25%) had suspected obstructive CAD on CTA of whom 400/445 patients (90%) underwent subsequent PET and ICA. CT-QFR was successfully analysed in 383/400 (96%) patients classifying 174/383 (45%) patients as having disease. In comparison, PET classified 130/383 (34%) patients as having disease. In total, obstructive CAD by ICA with FFR was identified in 162 (42%) patients. There was no significant difference in area under the receiver-operating characteristic curves for CT-QFR compared to the best performing PET metric (lowest vessel-specific MBF); 0.84 (95% CI 0.80–0.89) vs. 0.81 (0.77–0.85), p=0.19)) (Fig. 1). Overall diagnostic accuracy of CT-QFR versus PET was similar (78% (95% CI 74–82) vs. 77% (72–81), p=0.70. Sensitivities for CT-QFR and PET were 78% (71–84) and 63% (55–70), p<0.01, respectively, and specificities 78% (72–84) and 87% (82–91), p=0.01, respectively (Fig. 2). Three-vessel or left main disease on ICA was correctly identified in 30/31 patients by both CT-QFR and PET. Conclusion: In patients with suspected obstructive CAD by CTA, second-line CT-QFR was non-inferior to PET for discriminating obstructive CAD by invasive FFR; Although diagnostic accuracy was similar, CT-QFR demonstrated higher sensitivity while PET showed higher specificity Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Aarhus University PhD fellowshipRegion Mid Health Research Foundation